The sight eaudiobook - Clement-Davies, David (Sight, 2007)
In the wilds of Transylvania, a legend is about to be born as a wolf pack races through the bitter snows to find a birthing den for two cubs, one black, one white. In the birth of Fell, and his sister Larka, a race is on to defeat the wicked Morgra, and to come to terms with the extraordinary powers of The Sight.